Pengaruh Lingkungan Kerja Non Fisik Terhadap Disiplin Kerja Pegawai Pada Badan Perencanaan dan Pembangunan Daerah (BAPPEDA) Kota Bima - Aprianti, Aprianti; Wulandari, Wulandari (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
The purpose of the study was to determine and analyze the effect of the nonphysical work environment on the work discipline of employees at the Regional Planning and Development Agency of Bima City. This research uses associative research type. The research instrument used is a questionnaire used, namely a questionnaire with a Likert scale. The population in this study were all employees at the Regional Development Planning Agency (Bappeda) of Bima City, amounting to 53 people, 38 civil servants, 2 honorary k-2 workers, 11 contract workers, and 2 volunteers. The sampling technique used in this study is non-probability sampling. The considerations of researchers using purposive sampling are (1) To facilitate researchers in the sampling process; and (2) The researcher only examined employees with the status of civil servants (PNS), totaling 38 employees. The results showed that non-physical work environment variables had a positive and significant influence on employee work discipline.